Analysis of Government Functions in Indonesia - Herling Herling; Rifdan Rifdan; Sahade Sahade (Pendidikan Administrasi Perkantoran, Universitas Negeri Makassar, 2022)
Government is the spearhead in defending a country. One of the functions of government is service. The purpose of this article is to analyze the function of government in Indonesia in the public service sector. The approach used is literary studies. Data and information obtained through the website on open knowledge maps. The results of the study show that the function of government in the public service sector is actually the fulfillment of public welfare towards the fulfillment of the economic, social and cultural rights of citizens. So that social justice is realized in this country.